2004
DOI: 10.1111/j.0742-2822.2004.40027.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Mitral Regurgitation by Live Three‐Dimensional Transthoracic Echocardiographic Measurements of Vena Contracta Area

Abstract: We evaluated 44 consecutive patients who underwent standard two-dimensional (2D) and live three-dimensional (3D) transthoracic echocardiography (TTE), as well as left heart catheterization with left ventriculography. Mitral regurgitant vena contracta area (VCA) was obtained by 3D TTE by systematic and sequential cropping of the acquired 3D TTE data set. Assessment of mitral regurgitation (MR) by ventriculography was compared to measurements of VCA by 3D TTE and to 2D TTE measurements of MR jet area to left atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 10 publications
(39 reference statements)
2
77
0
1
Order By: Relevance
“…4 Recent advances in 3-dimensional (3D) echocardiography have allowed direct visualization and measurement of even highly asymmetrical EROA. Validation studies have demonstrated good correlation between EROA-3D echocardiography (EROA-3D) measurements and angiographic 5,6 and MRI measurements. 4,7,8 In addition, several recent studies using transthoracic echocardiography (TTE) have demonstrated less underestimation of EROA-3D compared with 2D vena contracta width (VCW-2D) and 2D PISA-derived measurements, suggesting improved accuracy in the estimation of mitral regurgitation severity.…”
Section: Clinical Perspective On P 700mentioning
confidence: 99%
“…4 Recent advances in 3-dimensional (3D) echocardiography have allowed direct visualization and measurement of even highly asymmetrical EROA. Validation studies have demonstrated good correlation between EROA-3D echocardiography (EROA-3D) measurements and angiographic 5,6 and MRI measurements. 4,7,8 In addition, several recent studies using transthoracic echocardiography (TTE) have demonstrated less underestimation of EROA-3D compared with 2D vena contracta width (VCW-2D) and 2D PISA-derived measurements, suggesting improved accuracy in the estimation of mitral regurgitation severity.…”
Section: Clinical Perspective On P 700mentioning
confidence: 99%
“…Real-time three-dimensional transthoracic echocardiography is a novel method of structural and functional analysis of the heart that permits real-time three dimensional investigation of the heart without using ionizing radiation, and is highly reproducible and easy to obtain [5][6][7][8][9][10][11][12][13][14][15][16] . It has a good cost-benefit ratio when compared with methods such as magnetic resonance imaging and also increases the possibility of identifying patients with advanced heart failure who can benefit from cardiac resynchronization therapy using biventricular pacemaker implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional echocardiography is more improved in relation to twodimensional echocardiography because it is not based on geometric inferences for the calculation of volumes of cardiac chambers, ventricular mass, and left ventricular ejection fraction, considering a limited number of observation planes [9][10][11][12][13][14][15][16] . An application of three-dimensional echocardiography that may have a great clinical impact is related to the indication and clinical follow-up of patients with NYHA functional class III and IV CHF undergoing cardiac resynchronization therapy with biventricular pacemaker.…”
mentioning
confidence: 99%
“…Note that in patients with asymmetric vena contracta shape, a biplane measurement in a 2-and 4-chamber view with a biplane vena contracta width of >0.8 cm has been proposed [14] and recently recommended to defi ne severe MR [8] [11] sectional area of the v ena contracta (VC) as the narrowest portion of the proximal regurgitant jet [73] [78]. However, this simplified assumption only holds when the EROA is nearly circular, and recent studies have indicated that the EROA is noncircular in most patients [78][79] [80], particularly when the VCW at the same time appears narrow in the 4-chamber view and broad in the 2-chamber view as in most cases of functional MR due to incomplete mitral leaflet closure (. Fig.…”
Section: Assessment Of Severity Of Mitral Regurgitationmentioning
confidence: 99%
“…Recently, color Doppler RT3DE was demonstrated in clinical studies to provide improved understanding and assessment of the asymmetric geometry of mitral regurgitant flow [81]. Khanna et al [80] initially demonstrated color Doppler RT3DE as a feasible method to provide direct visualization and planimetry of vena contracta area (VCA) of a regurgitant jet. Kahlert et al [14] showed that RT3DE overcomes the limitations of 2D measurements of vena contracta width (VCW) by direct assessment of the size and shape of the VCA and demonstrated the differences in VCA asymmetry among different etiologies of MR (.…”
Section: Assessment Of Severity Of Mitral Regurgitationmentioning
confidence: 99%